Influence of precipitating agents on thermodynamic parameters of protein crystallization solutions. Issue 9 (September 2016) - Stavros, Philemon; Saridakis, Emmanuel; Nounesis, George
ABSTRACT: X‐ray crystallography is the most powerful method for determining three‐dimensional structures of proteins to (near‐)atomic resolution, but protein crystallization is a poorly explained and often intractable phenomenon. Differential Scanning Calorimetry was used to measure the thermodynamic parameters (Δ G, Δ H, Δ S ) of temperature‐driven unfolding of two globular proteins, lysozyme, and ribonuclease A, in various salt solutions. The mixtures were categorized into those that were conducive to crystallization of the protein and those that were not. It was found that even fairly low salt concentrations had very large effects on thermodynamic parameters. High concentrations of salts conducive to crystallization stabilized the native folded forms of proteins, whereas high concentrations of salts that did not crystallize them tended to destabilize them. Considering the Δ H and TΔS contributions to the Δ G of unfolding separately, high concentrations of crystallizing salts were found to enthalpically stabilize and entropically destabilize the protein, and vice‐versa for the noncrystallizing salts. These observations suggest an explanation, in terms of protein stability and entropy of hydration, of why some salts are good crystallization agents for a given protein and others are not. This in turn provides theoretical insight into the process of protein crystallization, suggesting ways of predicting and controlling it. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 642–652, 2016.